2021
DOI: 10.1123/ijspp.2020-0713
|View full text |Cite
|
Sign up to set email alerts
|

Hamstring and Quadriceps Muscle Strength in Youth to Senior Elite Soccer: A Cross-Sectional Study Including 125 Players

Abstract: Purpose: Increasing age, high quadriceps strength, and low hamstring muscle strength are associated with hamstring strain injury in soccer. The authors investigated the age-related variation in maximal hamstring and quadriceps strength in male elite soccer players from under-13 (U-13) to the senior level. Methods: A total of 125 elite soccer players were included from a Danish professional soccer club and associated youth academy (first tier; U-13, n = 19; U-14, n = 16; U-15, n = 19; U-17, n = 24; U-19, n = 17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Previous literature indicates that hamstring strength imbalances may contribute to HSI incidence 19,20 . As these athletes age, strength increases and muscle flexibility decreases 33,34 . We demonstrated that imbalances are more prevalent among younger athletes; however, data in young soccer athletes indicate a greater degree of hamstring flexibility, which may be injury protective 33 .…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Previous literature indicates that hamstring strength imbalances may contribute to HSI incidence 19,20 . As these athletes age, strength increases and muscle flexibility decreases 33,34 . We demonstrated that imbalances are more prevalent among younger athletes; however, data in young soccer athletes indicate a greater degree of hamstring flexibility, which may be injury protective 33 .…”
Section: Discussionmentioning
confidence: 51%
“…19,20 As these athletes age, strength increases and muscle flexibility decreases. 33,34 We demonstrated that imbalances are more prevalent among younger athletes; however, data in young soccer athletes indicate a greater degree of hamstring flexibility, which may be injury protective. 33 These findings are consistent with prior reports that increasing age, despite decrease hamstring strength asymmetry with age, and hamstring stiffness are associated with hamstring injury.…”
Section: Discussionmentioning
confidence: 80%
“…Although our results showed that suture-bridge repair (SBR) was superior to TR at time zero in terms of the failure load and stiffness, their results suggest the importance of further investigation into how each repair procedure is coordinated with the other quadriceps during the subsequent healing process. Ishoi et al 14 reported that the mean quadriceps force among senior soccer players was 737.3 N. Since this value is much higher than the failure load after these 2 repair techniques, further clinical studies to investigate postoperative quadriceps muscle strength after these 2 repair methods are required.…”
Section: Discussionmentioning
confidence: 99%
“…In elite sport settings there is often a need to efficiently measure athletes' lower body strength in a short time frame, such as during periodic testing. 11,41 This can be achieved by using handheld dynamometers which easily accommodate various testing setups, such as unilateral hip adduction (ICC: 0.93) and abduction (ICC: 0.97). 13 In strong athletes, external fixation may be needed dependent on the tester's upper body strength to obtain valid measures, 15, 18 but this is not always feasible due to time constraints when large cohorts need testing.…”
Section: Maximal Isometric Strengthmentioning
confidence: 99%